2019
DOI: 10.17743/jaes.2019.0033
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Perception of Sound Source Distribution in the Median Plane

Abstract: Spatial perception of concurrently active sound sources was investigated in an exploratory listening experiment. Incoherent noise source distributions of varying spatial characteristics were presented from loudspeaker arrays in anechoic conditions. The arrays were coinciding with the ±45 • angular sectors in the frontal median and horizontal planes. The task of the immobile subjects was to report the directions of loudspeakers they perceived emitting sound. The results from median plane distributions suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…The ensemble width was restricted to fixed azimuth limits of ± 30°during the convolution procedure (this limit was adopted for consistency with our previous studies [7,9]), with the angles randomly selected for individual sources. Despite the relatively narrow intended ensemble width, informal listening tests undertaken by these authors showed that the perceived width for some stimuli was much wider than intended, spanning almost all semicircles (± 90°), which is consistent with the observation made by Pulkki et al [31]. HRTFs were not interpolated during the convolution procedure.…”
Section: Repository Of Binaural Music Recordingssupporting
confidence: 83%
“…The ensemble width was restricted to fixed azimuth limits of ± 30°during the convolution procedure (this limit was adopted for consistency with our previous studies [7,9]), with the angles randomly selected for individual sources. Despite the relatively narrow intended ensemble width, informal listening tests undertaken by these authors showed that the perceived width for some stimuli was much wider than intended, spanning almost all semicircles (± 90°), which is consistent with the observation made by Pulkki et al [31]. HRTFs were not interpolated during the convolution procedure.…”
Section: Repository Of Binaural Music Recordingssupporting
confidence: 83%
“…The reduction of the receiver to a virtual probe that does not maintain directional cues does not suffice a comprehensive auralisation output and must be expanded by a perception-equivalent model (e.g., a binaural processor, cf. Section 4.7.2) or an acoustic reproduction system that maintains perceptual cues (such as Vector-Base Amplitude Panning (VBAP) [Pul97], Higher-Order Ambisonics (HOA) [Ger83] or Wave Field Synthesis (WFS) [BVV93], cf. also Section 4.8).…”
Section: Iso 9613mentioning
confidence: 99%
“…Using the warped VRS directions, the contributions of the reflection coefficients of each of the orthogonal shoebox walls are calculated using vector base amplitude panning (VBAP; [47]) with the inverted (outside-pointing) wall normals as vector base. Eq.…”
Section: Extension To Inhomogeneous Boundary Conditions For Shoebox G...mentioning
confidence: 99%
“…Eq. ( 18) from [47] is therefore adapted to yield the contribution g k = [g 1 g 2 g 3 ] of the absorption coefficients of the three intersecting walls in each octant with the normal vectors n 1 , n 2 , n 3 to the filtering applied to a particular VRS with index k:…”
Section: Extension To Inhomogeneous Boundary Conditions For Shoebox G...mentioning
confidence: 99%